Sustainability of the anaerobic digestion biogas production system - Alina CRĂCIUN; Adrian Gheorghe ZUGRAVU; Andrei RUSU (ACROSS)
One of the main environmental problems of today's society is the continuous increase in the amount of organic waste. In many countries, the sustainable management of waste, as well as the prevention of its accumulation and the reduction of its quantity, have become major political priorities. This represents an important contribution to the common efforts to reduce pollution, greenhouse gas emissions and the mitigation of climate change at the global level. The past practices of uncontrolled waste disposal are no longer acceptable today. Even the storage on the garbage platform or the incineration of organic waste are not the best practices, because the protection standards have become much stricter nowadays, and the energy recovery and the recycling of nutrients and organic materials have become a necessary thing. The production of biogas through anaerobic digestion (AD) is considered to be the optimal treatment in the case of animal waste, as well as in that of a wide variety of organic waste suitable for this purpose, because in this way, the respective substrates are transformed into renewable energy and organic fertilizer for agriculture.